Prevalence of Physical Inactivity and Associated Factors: A study with military policemen from Macapá-AP/Brazil - Oliveira, Hêule Nilton Santos de; Pureza, Demilto Yamaguchi da; Materko, Wollner; Costa, Alisson Vieira; Alberto, Álvaro Adolf Duarte (International Journal of Advanced Engineering Research and Science, 2022)
The present study aimed to estimate the general prevalence of physical inactivity and identify associated factors. Participants were 162 military police officers from Macapá-AP/Brazil, of both sexes and aged between 23 and 54 years, 25.9% female. The assessment of the level of physical activity was obtained using the International Physical Activity Questionnaire (IPAQ) short version 8. The identification of association factors were obtained by the Socioeconomic Classification Questionnaire of the Brazilian Association of Research Companies (ABEP) version 2018, and by the Body Mass Index (BMI). Descriptive statistics were used to obtain the relative frequency in percentage with a confidence interval of 95%. The association between inactivity and associated factors was performed using the chi-square independence test and Spearman's correlation coefficient with a significance level of p < 0.05. It was identified that 27.8% of the studied sample is physically inactive and is associated with a lower economic class and with the perception of “poor/regular” health. Therefore, approximately three out of ten military police officers in the city of Macapá-AP/Brazil were classified as physically inactive and these rates are associated with socioeconomic and sociodemographic factors.